Support workers and the health professions in international perspective : the invisible providers of health care / edited by Mike Saks. - Saks, Mike (Sociology of health professions., 2020)
Health care support workers (HSWs) play a fundamental role in international health care systems, and yet they remain largely invisible. Despite this, the number of HSWs is growing fast as governments strive to combat illness and address social care issues in a world of finite resources. This original collection analyses the global experience of HSWs in the UK, Japan, Australia, Brazil, Canada, Portugal, Sweden and The Netherlands. Leading academics examine issues including the interface of HSWs with the health professions, regulatory practice risks, employment challenges and the dilemmas of an ageing population. Crucial future policy recommendations are also made for a world becoming increasingly dependent on HSWs.